DSC and TGA Measurements of Room Temperature Ionic Liquids (RTILs) Containing Ammonium Alum or Aluminum Nitrate with Amide Compounds - Abood, Hadi M A; Abid, Huda S (Al-Nahrain Journal of Science, 2018)
Characterization of some room temperature ionic liquids (RTILs) as thermal storage media and heat transfer fluids in thermal applications were investigated. Five ionic liquids prepared from ammonium alum NH4Al(SO4)2.12H2O as inorganic salt with urea NH2CONH2 or acetamide CH3CONH2 as organic compounds, and aluminum nitrate salt Al(NO3)3.9H2O either with urea or acetamide compounds in two mole ratios were investigated using Thermo-Gravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy and conductivity measurements. Thermo-physical properties such as enthalpy, heat capacity and thermal energy storage capacity were determined. It was found that ammonium alum: urea (USIL) in the mole ratio (1:5) and aluminum nitrate: acetamide (AN2IL) in the mole ratio (1:22) ionic liquids to be characterized with high density, wide liquid temperature range, high chemical stability, high heat capacity and high thermal energy storage capacity. Based on experimental results, it is concluded that ionic liquids could be considered as a candidate for liquid thermal storage media and heat transfer fluids.